KONSEP KEBAHAGIAAN MENURUT MASYARAKAT TAO: RELEVANSI AJARAN TAOISME DENGAN KEHIDUPAN MASA KINI - Insani, Satya Putri (Studia Sosia Religia, 2023)
This study explores information about new religious movements regarding the concept of happiness according to Taoist communities in Singkawang City, West Kalimantan Province. The existence of this research is interesting to uncover, because New religious movements are also part of the New Age Movement, which is a global phenomenon that often does not materialize, develop very quickly and expand. Taoism as a minority religion in a multi-ethnic city coexists side by side, where the essence of Taoism is to achieve happiness to unite with God and live in harmony with nature without defying the laws of nature whether it is still in harmony with today's life. The method used in this study is a descriptive research method of analysis with a qualitative approach by examining references and related sources about the subject matter (Library Research ). Data collected through scientific literature. This literature uses a variety of library sources. Based on the results of the data obtained, the concept of happiness Taoism still shows its relevance today, although perhaps not all of it is relevant. Today's civilization is strongly colored by the dominance of science and technology. With the help of science and technology, modern man seeks to unlock the secrets of nature and life, as well as nature and the laws that govern it. Technology can also limit human freedom, because humans have to adapt to the devices and systems that have been created. Taoism is able to warn and at the same time invite people to realize that after all humans cannot live outside nature and without the support of nature.